Channel model proposal for indoor relay-assisted power line communications - Wu, X.; Zhu, B.; Rong, Yue (The Institution of Engineering and Technology, 2018)
© The Institution of Engineering and Technology 2018. Due to its tree-like topology, the point-to-point (P2P) indoor power line communication (PLC) channel exhibits a similar broadcasting property as the wireless propagation channel shows. However, after relay nodes are introduced, the relayassisted PLC (RaPLC) channel shows some notable differences compared with its wireless counterpart. A lot of results about the relay-assisted wireless channel can be found in the literature, but the work of modelling RaPLC channel has rarely been discussed in detail. As the first attempt to fill this gap, we apply the ABCD method to compute the channel transfer function (CTF) of the RaPLC channel. It has been clarified that, in general, the CTF of RaPLC channel cannot be obtained as a cascade of two independent P2P PLC sub-channels located on two sides of the relay node. Also, it is shown that the challenge of generating CTF of the RaPLC channel can be transformed into a group of equivalent P2P PLC channel modelling tasks. Under the time-division duplexing constraint, the relay node changes its working mode from the receiving phase to the transmitting phase, which shows that the RaPLC channel is abruptly time-varying in nature. Following the hybrid bottom-up approach, a statistical channel model with a simple six-segment indoor power grid topology has been developed for simulation. Practical measurements and numerical examples verify our results.